THE ROLE OF LOCAL GOVERNMENT OF JAKARTA DC IN HANDLING SOCIAL WELFARE PROBLEMS – STREET CHILDREN - D. Farida Sinaga (Jurnal Ilmiah Ekonomi Bisnis, 2012)
Social welfare problems which is noted as Penyandang Masalah Kesejahteraan Sosial (PMKS) in Indonesia, is urgently needed to be solved. Jakarta Dean Capital (Jakarta DC) as promising city to every Indonesian citizens is the most troubled with PMKS. Hence local goverment is accused to handle PMKS problem by issuing various programs. The objective of the study therefore is to evaluate the role of local government in handling PMKS problem. Research design is constructed as field research method in three (3) locations PSAA. Study showed that local government should involve the relevant agencies such as Social Services, Satpol PP, Public Health Service and the Police in handling PMKS problems. Outreach result is suggested to be handed over to Social Institutions “Bina Insan Bangun Daya” for temporary shelter in order to classify type of PMKS. PMKS-Street Children types are referred to the Social Institutions “Anak Putra Utama.”Key Words : Jakarta DC, PMKS, local government, street children